Temperature dependent optical characterization of Ni-TiO2 thin films as potential photocatalytic material - Rajnarayan De; S. Maidul Haque; S. Tripathi; K. Divakar Rao; Ranveer Singh; T. Som; N. K. Sahoo (AIP Advances, 2017)
Along with other transition metal doped titanium dioxide materials, Ni-TiO2 is considered to be one of the most efficient materials for catalytic applications due to its suitable energy band positions in the electronic structure. The present manuscript explores the possibility of improving the photocatalytic activity of RF magnetron sputtered Ni-TiO2 films upon heat treatment. Optical, structural and morphological and photocatalytic properties of the films have been investigated in detail for as deposited and heat treated samples. Evolution of refractive index (RI) and total film thickness as estimated from spectroscopic ellipsometry characterization are found to be in agreement with the trend in density and total film thickness estimated from grazing incidence X-ray reflectivity measurement. Interestingly, the evolution of these macroscopic properties were found to be correlated with the corresponding microstructural modifications realized in terms of anatase to rutile phase transformation and appearance of a secondary phase namely NiTiO3 at high temperature. Corresponding morphological properties of the films were also found to be temperature dependent which leads to modifications in the grain structure. An appreciable reduction of optical band gap from 2.9 to 2.5 eV of Ni-TiO2 thin films was also observed as a result of post deposition heat treatment. Testing of photocatalytic activity of the films performed under UV illumination demonstrates heat treatment under atmospheric ambience to be an effective means to enhance the photocatalytic efficiency of transition metal doped titania samples.